Pengaruh Kompleksitas Operasi Perusahaan, Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Audit Delay (Study Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2013-2015) - Sutamat, Bangkit; , Dr. Triyono, SE, M.Si (2017)
The aim of this research was to analyzed the effect of complexity of operations of the company, profitability, leverage, and the firm size on audit delay. Population of this research was all of manufacturing firms listed in Indonesian Stock Exchange in period 2011-2015. The sampling method used purposive sampling method with the total sample as much as 135 companies. Analysis used by multiple regression methode. The results showed that the complexity of operations of the company and firm size have effect on audit delay while the leverage and profitability have no effect on audit delay. Keyword : audit delay, complexity of operations of the company, leverage, profitability, firm size.